Gender-Inclusive, -Responsive and -Transformative Agricultural Insurance: A Literature Review - Timu, Anne; Kramer, Berber (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This literature review uses a gender analysis framework proposed by Johnson et al. (2018) to explore the extent to which agricultural insurance reaches, benefits and empowers women and men. We find that most studies on gender and agricultural insurance focus on gender inclusivity by analyzing gender gaps in insurance reach and studying how to increase take-up among women. By contrast, limited attention has been paid to understanding gender equity in the distribution of insurance outcomes, that is, the extent to which insurance benefits and empowers women as much as men. We show that insurance programs can promote gender equity in benefits by providing quality insurance products that are beneficial to both men and women, and through long-term monitoring of individual outcomes measured within households using gender-disaggregated data. Insurance programs can support gender empowerment by ensuring that contracts purchased by women are registered under their names and payouts are subsequently paid to their accounts, by bundling insurance with empowerment programs, and by preserving and promoting informal mutual assistance group activities and membership. We then draw on a case study in Kenya to illustrate how this framework can be applied to design more gender-inclusive, -responsive and -transformative insurance schemes.